Pelatihan Kewirausahaan Syariah bagi Remaja Masjid DKM Al-Ikhlas sebagai Upaya Meningkatkan Kemandirian Ekonomi Berbasis Islam - Sumiah Nasution; Ismail; Ismail Dwi Cahyo; Ulfa Pauziah (Jurnal Ragam Pengabdian, 2025)
Economic independence among youth is a crucial aspect of community development. Sharia-based entrepreneurship training serves as a strategic approach to equip mosque youth with Islamic values and entrepreneurial skills. This community engagement program was conducted at Al-Ikhlas Mosque, involving 25 youth participants. The training method included interactive lectures, case studies, and business proposal simulations using Islamic contract schemes. Based on pre- and post-test results, participants' average score significantly increased from 58.4 to 84.7. The final evaluation revealed that 96% of participants were satisfied with the training content and delivery, and 88% expressed their willingness to recommend the program to others. This program also successfully established a youth sharia entrepreneur community within the mosque. The findings demonstrate that mosques can function as centers of Islamic-based economic empowerment for youth.